Primary Microcephaly, Impaired DNA Replication, and Genomic Instability Caused by Compound Heterozygous ATR Mutations. Issue 2 (20th December 2012) - Mokrani‐Benhelli, Houda; Gaillard, Laetitia; Biasutto, Patricia; Le Guen, Tangui; Touzot, Fabien; Vasquez, Nadia; Komatsu, Jun; Conseiller, Emmanuel; Pïcard, Capucine; Gluckman, Eliane; Francannet, Christine; Fischer, Alain; et al.
<x xml:space="preserve">Abstract</x> We here report the first patient with compound heterozygous ATR mutations. By using DNA combing technology we demonstrate that ATR‐deficient cells exhibit a profound spontaneous alteration of DNA replication parameters. Moreover, we show that the genomic instability caused by ATR deficiency is exacerbated by ATM inhibition. Collectively, our results emphasize the crucial role for ATR in the control of DNA replication, and reinforce the complementary and non redundant contributions of ATM and ATR in human cells to warrant genome integrity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>